Astaxanthin Supplementation Improves the Subsequent Developmental Competence of Vitrified Porcine Zygotes - Xiang, Decai; Jia, Baoyu; Zhang, Bin; Liang, Jiachong; Hong, Qionghua; Wei, Hongjiang; Wu, Guoquan (Frontiers in Veterinary Science, 2022)
Cryopreservation of embryos has been confirmed to cause oxidative stress as a factor responsible for impaired developmental competence. Currently, astaxanthin (Ax) raises considerable interest as a strong exogenous antioxidant and for its potential in reproductive biology. The present study aimed to investigate the beneficial effects of Ax supplementation during in vitro culture of vitrified porcine zygotes and the possible underlying mechanisms. First, the parthenogenetic zygotes were submitted to vitrification and then cultured in the medium added with various concentrations of Ax (0, 0.5, 1.5, and 2.5 μM). Supplementation of 1.5 μM Ax achieved the highest blastocyst yield and was considered as the optimal concentration. This concentration also improved the blastocyst formation rate of vitrified cloned zygotes. Moreover, the vitrified parthenogenetic zygotes cultured with Ax exhibited significantly increased mRNA expression of CDX2, SOD2, and GPX4 in their blastocysts. We further analyzed oxidative stress, mitochondrial and lysosomal function in the 4-cell embryos and blastocysts derived from parthenogenetic zygotes. For the 4-cell embryos, vitrification disturbed the levels of reactive oxygen species (ROS) and glutathione (GSH), and the activities of mitochondria, lysosome and cathepsin B, and Ax supplementation could fully or partially rescue these values. The blastocysts obtained from vitrified zygotes showed significantly reduced ATP content and elevated cathepsin B activity, which also was recovered by Ax supplementation. There were no significant differences in other parameters mentioned above for the resultant blastocysts. Furthermore, the addition of Ax significantly enhanced mitochondrial activity and reduced lysosomal activity in resultant blastocysts. In conclusion, these findings revealed that Ax supplementation during the culture period improved subsequent embryonic development and quality of porcine zygotes after vitrification and might be used to ameliorate the recovery culture condition for vitrified embryos.